Strengthening conflict sensitivity in Kenya’s county climate change fund: Wajir County - Medina, Leonardo; Schapendonk, Frans; Jaskolski, Martina; Osumba, Joab; Jebiwott, Alice; Mutuku, Munini; Takaindisa, Joyce; Giti, Daniel (2025)
This policy brief analyzes the role of Kenya’s County Climate Change Fund (CCCF) in advancing conflict-sensitive adaptation in Wajir County, an arid region where livelihoods depend heavily on pastoralism and resource competition is often entangled with clan dynamics. The study finds that Wajir’s CCCF has fostered inclusive decision-making through Ward Climate Change Planning Committees (WCCPCs), participatory barazas, and strong links with peace committees, rangeland groups, and water associations. Continuous funding streams and transparency measures have bolstered accountability and community trust. Moreover, local peacebuilders and elders play active roles in preventing disputes around contested sites, demonstrating how adaptation can be anchored in customary governance. Still, challenges persist: coordination with formal peace and security actors remains ad hoc, administrative budgets are too limited to sustain capacity, gender norms constrain women’s influence, and monitoring systems rarely track peace outcomes. The brief recommends formalizing peace actor engagement, strengthening administrative resourcing, documenting local lessons, and expanding outcome-oriented evaluation. Wajir’s experience shows that conflict-sensitive adaptation is essential in fragile pastoralist settings, offering pathways to resilience that reinforce both social cohesion and climate security.